Pharmacokinetics of isoniazid with or without ofloxacin - Brown, Sinyeofori A; Ezejiofor, Ndidiamaka A; Orisakwe, Orish E (International Current Pharmaceutical Journal, 2012)
Objective of the resent study was to determine the effect of ofloxacin (OXC) on the pharmacokinetics of isoniazid (INH). Five healthy volunteers aged 18 39 years participated in this study after an informed consent. The study was carried out in two phases with an interval of one-week drug wash out period in between phases. In phase one (INH alone), each subject received 300mg of isoniazid (INH) with 350ml of water after an overnight fast. The subjects were made to fast 2 hours post drug. In phase two (INH + OXC), each subject was administered with 300mg of INH in combination with 200mg of OXC observing all the protocol in phase one. The concentration of INH in plasma, saliva and urine of the subjects at predetermined time intervals were measured spectrophotometrically in the two phases over a period of 0 - 48 hours. Various pharmacokinetics parameters were calculated. From the study it is evident that Ofloxacin (OXC) increased the rate and extent of absorption of isoniazid. The absorption half-life (t1/2a) and the maximum concentration and absorption time (Cmax, Tmax) of isoniazid (INH) were increased in the presence of OXC. The urinary excretion of isoniazid was also increased by ofloxacin. The salivary concentration of isoniazid was less than the corresponding plasma drug concentrations, a pattern also found in similar studies. Thus it can be concluded that Ofloxacin increases absorption kinetics and urinary excretion of Isoniazid. DOI: http://dx.doi.org/10.3329/icpj.v1i12.12449 International Current Pharmaceutical Journal 2012, 1(12): 403-409